Functional divergence of the duplicated BrrCBL2.1 and BrrCBL2.2 genes in turnip (Brassica rapa var. rapa) - Qingwen Zeng; Haotong Kang; Xiangxiang Kong; Yifan Cai; Zhiyu Chen; Fanfan Lin; Tianping Huang; Yunqiang Yang; Xin Yin; Yanling Yue; Yongping Yang (Plant Gene, 2026)

Acquisition and temporal transcriptomic characteristics of cambial meristematic cells in Camptotheca acuminata under in vitro culture conditions - Yundan Xiong; Shuang Yu; Jiale Sun; Zhiyu Chen; Fanfan Lin; Yifan Cai; Tianping Huang; Xin Yin; Yan Zheng; Yunqiang Yang; Xiangxiang Kong; Yongping Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Nuclear transport factor IPO4 modifies localization by PCV2 and facilitates viral replication - Cui Lin; Chengcheng Wu; Fanfan Zhang; Na Li; Haiqin Li; Lihan Tao; Jia Tan; Yanbing Zeng; Shaopei Fang; Quanyong Zhou (Veterinary Microbiology, 2025)

Impact of filtration processes on the key chemical components of Shanxi aged vinegar - Ping Lin; Fanfan Lang; Yufeng Yan; Jian Chen; Zheng Peng; Juan Zhang (Food Bioscience, 2025)

Recent advances in 3D cell culture models in cancer drug development - Yae Sol Cha; Alvin Michaels; Janney Z. Wang; Yihe Niu; Yipeng Lin; Ling Zhu; Xue Zhu; Ke Wang; Michael Murray; Fanfan Zhou (Journal of Pharmaceutical Investigation, 2025)
Background In vitro cell culture models are widely used in cancer drug development. However, traditional two-dimensional (2D) models do not replicate the complex characteristics of the tumour microenvironment. Three-dimensional (3D) culture models have been used to prepare cell spheroids that are increasingly used in drug screening and evaluation due to their greater capacity to mimic tumour properties. Area covered This review discusses the methods used to generate 3D cell systems and their applications in cancer research. There are several methods used in the generation of 3D culture models, including forced floating and matrix-based methods. However, bioprinting technologies have emerged more recently as novel approaches to generate 3D culture models that can better mimic tumour physiology. 3D models are used to evaluate the activities of drugs in a wide variety of cancer types, although they have not yet been widely applied in the case of rarer cancers. Expert opinion 3D culture models have a number of desirable features that are advantageous in anti-cancer drug development. However, some methods of spheroid production have issues of inherent non-reproducibility and inconsistency, while bioprinting technology generally has more favourable features. Thus, newer optimised technologies will improve the physiochemical properties of spheroids, which may promote their application in cancer drug development.

The plant retromer components SNXs bind to ATG8 and CLASP to mediate autophagosome movement along microtubules - Yanglan Liao; Xibao Li; Wenlong Ma; Xinyi Lin; Jiayi Kuang; Xuanang Zheng; Zien Li; Fanfan Qiao; Chuanliang Liu; Jun Zhou; Faqiang Li; Ruixi Li; et al. (Molecular Plant, 2025)

Interaction of microalgae, nitrogen and arsenic in a water environment co-polluted by nitrogen and arsenic: current knowledge and future perspectives - Youwen Li; Xinxin Zhao; Zhaoqi Zhong; Fanfan Ju; Hui Liu; Ning Lin; Xianghao Zha (Aquatic Ecology, 2025)

Influence of rhizospheric symbiotic microorganisms on the behavioural effects of antimony in soil-plant system: Insights from a proteomic perspective - Min Zhou; Hui Li; Lin Xi; Feng Shi; Xinru Li; Fanfan Wang; Xuesong Liu; Hailei Su; Yuan Wei (Journal of Hazardous Materials, 2024)

Development and assessment of a three-field subchannel code for thermo-hydraulic transient analysis under reflood conditions - Lin Chen; Hao Zhang; Yingran Guo; FanFan Zhou; Yanhua Yang; Meng Zhao (Annals of Nuclear Energy, 2024)

Enhancing pakchoi (Brassica chinensis L.) agriculture with magnetized-ionized brackish water and organic fertilizers: A sustainable approach to soil quality and crop yield optimization - Shudong Lin; Quanjiu Wang; Kai Wei; Yan Sun; Fanfan Shao; Qingyuan Lei; Mingjiang Deng (Journal of Cleaner Production, 2024)

Numerical investigation of the maximum temperature zone for liquid–vapour flow during reflooding - Yixuan Cheng; Hao Zhang; Meng Zhao; Lin Chen; Fanfan Zhou; Yanhua Yang (Annals of Nuclear Energy, 2024)

A novel hybrid simulated annealing algorithm for colored bottleneck traveling salesman problem - Xueshi Dong; Qing Lin; Fanfan Shen; Qingteng Guo; Qingshun Li (Swarm and Evolutionary Computation, 2023)

Enhancing acidification efficiency of vegetable wastes through heat shock pretreatment and initial pH regulation - Fanfan Cai; Ming Lin; Ligong Wang; Chao Song; Yan Jin; Guangqing Liu; Chang Chen (Environmental Science and Pollution Research, 2023)

Identification and prediction of climate factors based on factor analysis and a grey prediction model in China - Shudong Lin; Kai Wei; Qingyuan Lei; Fanfan Shao; Quanjiu Wang; Mingjiang Deng; Lijun Su (Environmental Monitoring and Assessment, 2023)

Synergistic effects of biochar and carboxymethyl cellulose sodium (CMC) applications on improving water retention and aggregate stability in desert soils - Fanfan Shao; Senlin Zeng; Quanjiu Wang; Wanghai Tao; Junhu Wu; Lijun Su; Haokui Yan; Yibo Zhang; Shudong Lin (Journal of Environmental Management, 2023)

Combined effects of the earthworm casts application and fallow time on runoff and sediment loss by raindrop splashing in the Loess Plateau, China - Fanfan Shao; Wanghai Tao; Junhu Wu; Shudong Lin; Quanjiu Wang (Journal of Environmental Management, 2023)

Possible seismo-ionospheric precursor of the 12 February 2014 Yutian earthquake in China - Jian Yang; Yiyan Zhou; Jian Lin; Fanfan Su; Wenbin Shen (Journal of Earth System Science, 2019)

Detection and genetic characterization of porcine pegivirus from pigs in China - Dan Lei; Yu Ye; Kun Lin; Fanfan Zhang; Dongyan Huang; Kai Li; Weifeng Yuan; Qiong Wu; Zhen Ding; Leyi Wang; Deping Song; Yuxin Tang (Virus Genes, 2019)

Statistical Analysis of TEC Anomalies Prior to M6.0+ Earthquakes During 2003–2014 - Fuying Zhu; Fanfan Su; Jian Lin (Pure and Applied Geophysics, 2018)